Assessment of pre‐treatment technologies for bioethanol production from sugarcane bagasse considering economics and environmental impact. Issue 2 (20th December 2016) - Crimes, J.; Isafiade, A.J.; Fraser, D.M.; Short, M.; Bonomi, A.
Abstract: This work involves the assessment of various pre‐treatment methods for the production of bioethanol in South Africa from sugarcane bagasse. The possibility of producing methane was also considered. The pre‐treatment methods that have been modelled are acid pre‐hydrolysis, steam explosion (acid‐catalysed and un‐catalysed), delignification with sodium hydroxide, acid hydrolysis and enzymatic hydrolysis. These pre‐treatment options were arranged in a superstructure, and optimization was performed by decomposing the superstructure into eight possible flowsheets. These flowsheets were then optimized in General Algebraic Modelling Systems by using economic and environmental objective functions sequentially. The solution space was used to evaluate the possible flowsheets in terms of both objectives. Steam explosion pre‐treatment would be recommended for the production of only methane. Acid hydrolysis can be added to steam explosion in order to produce glucose (for bioethanol production), and this increases profitability and reduces environmental impact of the steam explosion only flowsheet; however, the glucose flowrate from the steam explosion with acid hydrolysis flowsheet is low. The steam explosion with enzymatic hydrolysis flowsheet would be recommended to produce a higher glucose flowrate; however, the environmental impact of this flowsheet may be large if the electricity consumption of enzyme production is large. Copyright © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.